2020
DOI: 10.1037/pro0000306
|View full text |Cite
|
Sign up to set email alerts
|

The role of personal, professional, and psychological factors in therapists’ resilience.

Abstract: The aim of the present study was to investigate the factors that help therapists maintain their resilience to work stressors. Participants were Greek mental health practitioners (N = 163) who were approached through the National Organization of Psychotherapy in Greece as well as through several Greek online professional groups. Participants completed online measures of professional quality of life, counseling self-efficacy, empathy, and the five dimensions of Seligman’s well-being model (positive emotion, enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 67 publications
4
25
0
8
Order By: Relevance
“…The same study showed that higher stress in therapists' personal lives was associated with their tendency to use avoidant coping strategies when experiencing difficulties in practice, while therapists' use of avoidant coping has been associated with less beneficial outcomes for clients in other studies (Heinonen et al, 2014). These findings demonstrate that therapists' personal distress can have negative consequences for their therapeutic work (see also Lakioti et al, 2020). There likely are different mechanisms by which this may occur.…”
Section: Psychotherapists' Emotional Burdens and Distressmentioning
confidence: 87%
See 1 more Smart Citation
“…The same study showed that higher stress in therapists' personal lives was associated with their tendency to use avoidant coping strategies when experiencing difficulties in practice, while therapists' use of avoidant coping has been associated with less beneficial outcomes for clients in other studies (Heinonen et al, 2014). These findings demonstrate that therapists' personal distress can have negative consequences for their therapeutic work (see also Lakioti et al, 2020). There likely are different mechanisms by which this may occur.…”
Section: Psychotherapists' Emotional Burdens and Distressmentioning
confidence: 87%
“…Therapist work satisfaction is a vital element in their sense of wellbeing and can even be felt by patients to the extent that it affects their progress in therapy (Delgadillo et al, 2018). When studying work-related predictors of occupational burnout, Steel et al (2018) showed that higher work demands and lack of autonomy were also salient predictors of therapist burnout (see too Lakioti et al, 2020).…”
Section: Sources Of Burdens and Distressmentioning
confidence: 99%
“…In Greece, studies concerning psychological resilience have focused on its relationships with protective factors against adversities, such as experiencing positive emotions (Karampas et al, 2016), meaning in life, positive relationships (Lakioti et al, 2020), locus of control, coping strategies (Leontopoulou, 2006), positive identity development (Motti-Stefanidi, 2015), and positive school climate (Hatzichristou et al, 2014(Hatzichristou et al, , 2017.…”
Section: Psychological Resiliencementioning
confidence: 99%
“…Secondly, it dissociates psychotherapy from the medical model, according to which all symptoms are mainly due to brain disorders. Third, it widens the therapeutic effect by adding to the elimination of symptoms the achievement of psychological wellbeing and, fourth, it minimizes the negative impact of the psychotherapeutic process on the therapist, who is constantly burdened with negative experiences (Lakioti et al, 2020;Rashid & Seligman, 2018).…”
Section: Positive Interventions and Psychotherapymentioning
confidence: 99%
“…(Litam, Ausloos, & Harrichand, 2021;Wezyk et.al, 2021). Because mental health specialists are classified as key workers in this field, they are now experiencing more intense mental work load than ever before due to the specifics of working with different categories of trauma victims (Lakioti, Stalikas & Pezirkianidis, 2020;David, 2012). This is primarily due to the specifics of providing psychological assistance, which is characterized by long-term and consistent impact of traumatic life events and emotional involvement in a relationship with a person experiencing the consequences of trauma.…”
Section: Introductionmentioning
confidence: 99%